POSITIVE REINFORCEMENT IN INDIVIDUAL COUNSELING TO REDUCE AGGRESSION IN VISUALLY IMPAIRED STUDENTS - Sari, Liza Purma; Jannati, Zhila; Marianti, Lena (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to determine the application of individual counseling services with positive reinforcement techniques in overcoming the aggressive behavior of visually impaired students in client "A" at SLB-A PRPCN Palembang. Aggressive behavior is behavior that involves the act of attacking, hurting, or harming another person, either verbally or physically. The approach used in this study is a qualitative approach using a case study research method. The data collection techniques used in this study are observation, interview, and documentation methods. Meanwhile, the data analysis technique used in this study is the data analysis method of Robert K Yin's case study. The results of the study showed that the aggressive behavior that existed in client "A" was the desire to hurt someone with objects, hurt others physically, the client also often spoke harshly, was angry uncontrollably, and often quarreled because he did not accept being reprimanded that he was doing something wrong. The results after being given the application of positive reinforcement, client "A" has had significant changes, namely where client "A" looks calmer and more patient in dealing with various situations. The client can distinguish between what is good and bad for him, as well as stay away from unhelpful behavior, such as insulting or pranking others. Based on the results of the application of individual counseling with positive reinforcement techniques to overcome aggressive behavior in client "A", it can be concluded that this technique is effective can overcoming his aggressive behavior.